The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1210/jc.2012-3092
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Screening Score for Undiagnosed Diabetes and Its Application in Estimating Absolute Risk of Future Type 2 Diabetes in Japan: Toranomon Hospital Health Management Center Study 10 (TOPICS 10)

Abstract: Our algorithm could serve as a self-assessment tool for undiagnosed diabetic patients needing timely medical care and as a prognostic tool for individuals without present diabetes who must be closely followed up to prevent future diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Even though the discrimination of another two algorithms was greater than that of our algorithms, those algorithms did not achieve a good trade‐off between sensitivity and specificity at predefined optimal cut‐off values. For both algorithms, the specificities were unacceptably low although the sensitivities were at least 90%. Hence, a high degree of discrimination does not necessarily lead to reasonable performance at recommended cut‐off values.…”
Section: Discussionmentioning
confidence: 63%
“…Even though the discrimination of another two algorithms was greater than that of our algorithms, those algorithms did not achieve a good trade‐off between sensitivity and specificity at predefined optimal cut‐off values. For both algorithms, the specificities were unacceptably low although the sensitivities were at least 90%. Hence, a high degree of discrimination does not necessarily lead to reasonable performance at recommended cut‐off values.…”
Section: Discussionmentioning
confidence: 63%
“…An elevation in blood pressure, even within a high normal level, is associated with insulin resistance [9,10], and a high normal blood pressure and hypertension are associated with an elevated risk of developing type 2 diabetes [11][12][13]. Moreover, Kim et al reported that in addition to subjects with hypertension at the time of registration, subjects who later developed prehypertension or hypertension were also at risk for developing type 2 diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the factors associated with undiagnosed diabetes [7,19,20], but not the factors for untreated diabetes. Although the factors that are associated with untreated and undiagnosed diabetes may differ, it is relevant to compare our results with previous studies that examined the factors associated with undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that were identified by our study, such as sex, current smoking, hypertension, and exercise habits, were also commonly used to detect undiagnosed diabetes. In previous studies, family history of diabetes was another strong predictor of undiagnosed diabetes [7,19], although this information was not available for our study. Although decreased HDL cholesterol and increased non-HDL cholesterol levels were predictors of untreated diabetes in our study, lipid levels have rarely been used to detect undiagnosed diabetes [7,19], possibly because blood testing is needed to evaluate lipid levels.…”
Section: Discussionmentioning
confidence: 99%